2016
DOI: 10.1177/0031512516682668
|View full text |Cite
|
Sign up to set email alerts
|

Human–Human Handover Tasks and How Distance and Object Mass Matter

Abstract: We investigated the coordination between two individuals during object handovers. Ten participants (eight males, two females; 26.0 ± 5.0 years, 72.7 ± 13.5 kg, 1.73 ± 0.8 m) arranged in pairs (a giver and a receiver), passed an object from the giver to the receiver at a self-selected speed. A motion capture system quantified the giver and the receiver's motion simultaneously. Three interpersonal distances and three object masses were chosen to study the handover. We hypothesized that (a) the handover occurs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…We observed that the handover positions can be explained surprisingly well by a linear function considering the distance from their partner, and the participant’s, as well as their partner’s, physical and social characteristics (Table 1, Fig 3). While previous studies have proposed models for describing the handover position considering the physical characteristics of the participant [11] as well the inter-personal distance [15], our study is probably the first to show the influence of partner characteristics, especially social dominance, in human handovers (see third bar in Fig 3a and 3b). This result suggests that human participants can immediately estimate the preferred handover positions of partners they have just met.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…We observed that the handover positions can be explained surprisingly well by a linear function considering the distance from their partner, and the participant’s, as well as their partner’s, physical and social characteristics (Table 1, Fig 3). While previous studies have proposed models for describing the handover position considering the physical characteristics of the participant [11] as well the inter-personal distance [15], our study is probably the first to show the influence of partner characteristics, especially social dominance, in human handovers (see third bar in Fig 3a and 3b). This result suggests that human participants can immediately estimate the preferred handover positions of partners they have just met.…”
Section: Discussionmentioning
confidence: 79%
“…The experiment started with the measurement of the arm lengths of the partner and participant, which were used to define the distance AL (as in [15]). A mark on the floor indicated the position where the receiver should stand, while three marks were made for the giver at three inter-personal distances (or IDs) of 0.7AL, AL and 1.3 AL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human hand is involved in many daily human activities. The hand is connected to the forearm by the wrist joint which contributes to its special orientation facilitating the manipulation of objects (Hansen et al 2017). However, the wrist joint has a complex organisation of carpal bones.…”
Section: Introductionmentioning
confidence: 99%